Methodological approach for the assessment of environmental effects of agroforestry at the landscape scale. - Palma, João H. N.; Graves, Anil; Burgess, Paul J.; Keesman, K. J.; van Keulen, Herman; Mayus, Martina; Reisner, Y.; Herzog, Felix (Elsevier, 2007)
Silvoarable agroforestry, the deliberate combined use of trees and arable crops on the same area of land, has been proposed in order to improve the environmental performance of agricultural systems in Europe. Based on existing models and algorithms, we developed a method to predict the environmental effects of SAF at a farm and landscape scale. The method is comprised of an assessment of soil erosion, nitrogen leaching, carbon sequestration, and landscape diversity and allowed the comparison of the environmental performance of SAF with arable systems using these four indicators.
Keywords: Erosion; Nitrogen leaching; Carbon sequestration; Landscape diversity; Modeling; Alley cropping